2016
DOI: 10.1128/aac.00975-16
|View full text |Cite
|
Sign up to set email alerts
|

Short Palate, Lung, and Nasal Epithelial Clone 1 Has Antimicrobial and Antibiofilm Activities against the Burkholderia cepacia Complex

Abstract: The opportunistic bacteria of the Burkholderia cepacia complex (Bcc) are extremely pathogenic to cystic fibrosis (CF) patients, and acquisition of Bcc bacteria is associated with a significant increase in mortality. Treatment of Bcc infections is difficult because the bacteria are multidrug resistant and able to survive in biofilms. Short palate, lung, and nasal epithelial clone 1 (SPLUNC1) is an innate defense protein that is secreted by the upper airways and pharynx. While SPLUNC1 is known to have antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…6c). This structural observation supports the hypothesis that the 4 motif is involved in the unique antibacterial activities of the BPIFA1 proteins, which have not been reported for latherin or Der f 7 (Walton et al, 2016;Ahmad et al, 2016;Emsley & Cowtan, 2004;Tan et al, 2012).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…6c). This structural observation supports the hypothesis that the 4 motif is involved in the unique antibacterial activities of the BPIFA1 proteins, which have not been reported for latherin or Der f 7 (Walton et al, 2016;Ahmad et al, 2016;Emsley & Cowtan, 2004;Tan et al, 2012).…”
Section: Resultssupporting
confidence: 86%
“…Bacterial permeability-increasing family member A1 (BPIFA1) is a member of the bacterial permeability-increasing (BPI) superfamily of proteins (Bingle et al, 2011), and has previously been known as short palate lung nasal epithelial clone 1 (SPLUNC1), secretory protein in upper respiratory tracts (SPURT), lung-specific X protein (LUNX) and nasopharyngeal carcinoma-related protein (NASG). BPIFA1 is one of the most abundantly secreted proteins in the upper airways of the lung, and demonstrates activities as a bacteriostatic agent, surfactant and lipopolysaccharidebinding factor (Liu et al, 2013;Di, 2011;Wei et al, 2014;Jiang et al, 2013;Chu et al, 2007;Walton et al, 2016;Ahmad et al, 2016). BPIFA1 employs these varied functions to maintain normal lung function by, for example, spreading fluid across the pulmonary epithelium and maintaining sterile airways (Tarran & Redinbo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that the activity of molecules such as the protease inhibitor SPLUNC1, which regulates antimicrobial peptides (AMPs) and shows itself antimicrobial activity [97], depends on optimal ASL pH [36, 98], as does the activity of AMPs themselves [34]. On a more general level, when pathogens enter the airways, they are recognised by epithelial cells that activate inflammatory pathways to recruit immune cells, specifically neutrophils, into the airway lumen to eradicate the infection.…”
Section: Role Of Cftr In the Lungsmentioning
confidence: 99%
“…More recent studies have shown that the Human Short Palate Lung Nasal Epithelial Clone 1 (SPLUNC1), which is a protein expressed in the upper airways of the lung, plays multiple roles in pulmonary innate immunity. These roles include: the direct inhibition of bacterial growth, the prevention of microbial biofilm formation and the regulation of other AMPs and antimicrobial proteins, such as LL-37, HBD-2 and lysozyme [173,174,175,176]. However, in CF, mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene leads to reduced HCO 3 − secretion and produces an abnormally acidic pH in ASL [177,178], which studies on humans and animal models have suggested can negatively affect the efficacy of ASL antimicrobial molecules and predispose CF airways to microbial infection (Figure 3) [165,179].…”
Section: An Overview Of Ph Dependent Peptides and Proteins With Anmentioning
confidence: 99%